2005
DOI: 10.1037/1099-9809.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Academic Attitudes and Achievement in Mexican-Origin Youths: Ethnic Identity, Other-Group Orientation, and Fatalism.

Abstract: This study tested the relationships among ethnic identity, other-group orientation, fatalism, and 2 dependent variables: attitude toward education and school, and grade point average (GPA). Mexican-origin adolescents (N = 222) completed the Multigroup Ethnic Identity Measure (J. S. Phinney, 1992), the fatalism scale of the Multiphasic Assessment of Cultural Constructs-Short Form (I. Cuellar, B. Arnold, & G. Gonzalez, 1995), and the attitude scale of the Learning and Study Strategies Inventory-High School (C. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…In a sample of Mexican-origin adolescents, Guzman et al (2005) found that othergroup orientation was positively related to grade point average. These studies, while promising, are preliminary and need to be replicated in order to feel more confident about their findings.…”
Section: Other-group Orientation and Academic Achievementmentioning
confidence: 96%
“…In a sample of Mexican-origin adolescents, Guzman et al (2005) found that othergroup orientation was positively related to grade point average. These studies, while promising, are preliminary and need to be replicated in order to feel more confident about their findings.…”
Section: Other-group Orientation and Academic Achievementmentioning
confidence: 96%
“…Two factors, fatalism (Basáñez et al, 2013;Guzmán, Santiago-Rivera, & Hasse, 2005) and perceived racial barriers (Wood et al, 2011), were barriers of motivation in this subcategory. The fourth subcategory is emotions related to learning.…”
Section: Plans For Higher Educationmentioning
confidence: 99%
“…This category is about ethnic minority student's identity and orientation toward their own ethnic minority culture or the majority culture in which they live. Ten factors were facilitators and positively related with motivation of ethnic minority students: majority acculturation (Lew et al, 1998), acculturation (Ramos & Sanchez, 1995), Anglo (majority) orientation (Flores et al, 2008), minority acculturation (Lew et al, 1998), ethnic (identity) centrality (Perreira et al, 2010), racial/ethnic identity (Shin, 2011), ethnic pride (Warner, 2008), othergroup orientation (Guzmán et al, 2005), ethnic affirmation and belonging (Perreira et al, 2010), and Africentric values (Shin, 2011). The factor acculturation in the included studies can be summarized as follows: "a process in which cultural behaviors and values are changed through contact with the dominant culture" (Ramos & Sanchez, 1995, p. 213).…”
Section: Plans For Higher Educationmentioning
confidence: 99%
“…For instance, in their study with adolescents of Mexican descent, Fuligni et al (2005) found a positive relationship between ethnic identity and positive academic attitudes. Conversely, Guzmán et al (2005) did not find an association between ethnic identity and positive academic attitudes in their sample of Mexican American high school students. A potential cause of the contradictory results may stem from different conceptualizations and measurement of ethnic identity.…”
mentioning
confidence: 59%